SPATIAL MORPHOLOGICAL ANALYSIS: DEVELOPMENT OF THE NORTH KREMBANGAN AREA, SURABAYA, INDONESIA - Gunawan, Eveelyn Febe; Rony Gunawan Sunaryo; Rully Damayanti (Jurusan Arsitektur - FTSP - Universitas Trisakti, 2024)
The North Krembangan area is an old city area in Surabaya, right next to the Kalimas River. This area has experienced several changes from time to time, both in terms of natural context, roads, blocks/lots, and buildings. These changes were influenced by several factors and actors, both from the Dutch government and from the Surabaya government due to the existence of several new needs that were no longer relevant in the conditions during the colonial era. Objectives: To identify the morphology of urban tissue in the North Krembangan area which consists of permanent, non-permanent elements and street front quality Methodology and Results: This research uses the urban tissue methodology by Romice et al as a theory that helps to analyze this area. Conclusion, Significance and Implications: This research found that although the North Krembangan area has relatively low street front quality, this area is still busy and active as a commercial center. Suggestions to improve the area were also made at the end of this research.